Grismadox elsneri sp. nov.—a new species of ant-resembling sac spider from the Bolivian orocline, with indirect evidence of species-specific mimicry (Araneae: Corinnidae: Castianeirinae) - Perger, Robert; Rubio, Gonzalo D.; Pett, Brogan L. (Zootaxa, 2022)
A new species of ant-resembling sac spider of the subfamily Castianeirinae, Grismadox elsneri sp. nov., is described from the Sub-Andean area of the Bolivian orocline. The species was collected from savanna grass along the edges of the Chiquitano forest and is a putative mimic of the carpenter ants Camponotus cf. crassus or C. cf. blandus.